Doing and Talking: People with Intellectual Disabilities' Handling of Challenges of Remote Communication. Issue 1 (2nd January 2022) - Kversøy, Kjartan; Alhassan, Abdul-Razak; Kellems, Ryan; Kversøy, Sofie; Cusworth, Zackery
ABSTRACT: This article is about the challenge of communication via smartphones and tablets by people with intellectual disabilities (ID). We will give special attention to persons that struggle with verbal communication. One of our co-researchers, the fourth author, has a severe ID. She cannot read, write or use voice assisted technology in any functional manner. As a result of many years of collaboration, and the need for solutions in connection with the challenges with COVID-19, she and her family have developed ways of remote communication that can be mastered both by the person with an ID and the majority (those without similar disabilities). We call it doing and talking . Successful remote communication not only depends on technology and how to use it, but also on communication strategies that both work for the person with an ID and the majority. It is often the case that people with ID are expected to learn the skills necessary to adapt to the majority. We will show that success is just as much a question of the majority learning new skills and strategies that can make real inclusion and collaboration possible.